Butler on Wittig: From One Radical to Another Regarding Strategies of Emancipation - February, Tamlyn (The Stellenbosch Socratic Journal, 2022)
Judith Butler and Monique Wittig are two feminist philosophers with many similarities but also crucial differences. Wittig's starting point is the materiality of language where she posits that language has a dual function. It can affirm absolute reciprocity and equality among all speaking subjects in Being, but it can also institute artificial differences such as gender and sex. For Wittig, sex is a political category that establishes heterosexual society not in a binary way but in a way that particularises women as "the sex" while men are universal subjects in Being. Wittig calls for emancipation through a two-pronged lesbian revolution to obliterate sexual difference. Although Butler agrees with Wittig on the materiality of language, the political nature of sex, and that there is no natural category of "women", they critique and differ from Wittig on two fundamental bases. The first is that Wittig uncritically invokes the metaphysics of substance with the concepts of Being and the subject despite it being the basis of the heterosexual matrix. The second is Wittig's emancipation strategy of revolution over Butler's strategy of redeployment. This paper will discuss Wittig, Butler's critique of Wittig to articulate their own theory of gender performativity, and the more primary point that Butler does not argue for full-scale revolution. Rather, their emancipation strategy from heterosexual society is more radical as it aims to trouble all identities, and the notion of identity itself to make space for the legitimacy and recognition of "impossible" identities.